Genomic breed composition of pure registered Brazilian Gir - Milanesi, M. [UNESP]; Obrien, A. M. Perez; Utsunomiya, A. T.; Feres, L. F.; Sonstegard, T. S.; Garcia, J. F. [UNESP] (Springer, 2022)
Introduction Gir is a Bos indicus breed originally from India, first imported to Brazil in 1850. High-performance Dairy Gir has been systematically selected in Brazil from its arrival. Since the major phenotypic difference between Gir in India and Brazil is a higher milk production in the former, it is speculated that Brazilian Gir was strategically crossed with Holstein or another Bos taurus to improve milk yield. This study evaluated the purity of Brazilian Gir breed stocks from BASA Farms in Brazil, trying to identify possible admixture events with other cattle breeds based on DNA analysis. Materials and methods The population included 1061 pure registered individuals genotyped using two commercial platforms with 37 k and 25 k SNPs. Admixture analysis was performed individually to estimate levels of genomic composition derived from six different reference populations, three indicine and three taurine breeds. Results A Gir ancestry of 99% or higher was found for 94.2% of the population, while the remaining showed levels of non-Gir ancestry up to 6.8%. Only five individuals were identified with possible taurine ancestry, all of them exhibiting levels lower than 2%. The remaining non-Gir ancestry identified was derived from indicine breeds. The levels of admixture observed in the population were from low to non-detectable. No consistent patterns of admixture were observed indicating sustained introgression of taurine lines as means of genetic improvement. Conclusion According to these results, genetic improvement achieved by Brazilian Gir breeders is the result of within-breed selection methods applied intensively over the past five decades, rather than the result from sustained introgression.
Keywords: Bos indicus; Admixture; Breed purity; Introgression